Case Report: Dual-lumen microcatheter-facilitated wiring technique to correctly access a protruded aorto-ostial stent: a case series - Kim, Seok Hyun; Chun, Kook Jin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPercutaneous coronary intervention (PCI) through the aorto-ostial coronary stent that is protruding into the aorta remains a technical challenge because of the poor coaxial alignment of the guiding catheter and the inability to advance the guidewire into the distal vessel through the stent's central lumen. In this article, we introduce a dual-lumen microcatheter–facilitated wiring technique performed on two patients to overcome this difficulty.Case summaryThe first case was a 75-year-old man who presented with chest pain. He was diagnosed with an unstable angina, and coronary angiography showed near-total in-stent occlusion of the previously placed stent protruding into the aorta. Despite several attempts, the guidewire passed through the side strut of the stent instead of the central stent lumen. Thus, we placed the tip of the microcatheter proximally to the side strut, outside the stent. Then, a second wire was passed through the central lumen successfully. After confirming the wire's position via intravascular ultrasound, we inflated a drug-eluting balloon, subsequently obtaining a successful angiographic result. The second case was a 78-year-old woman diagnosed with non-ST segment elevation myocardial infarction. Coronary angiography revealed tight stenosis at the ostial left anterior descending artery with a previous stent deployed from the left main to the circumflex artery. Owing to the excessive overhanging stent into the aorta, the wire could not be advanced into the stent's central lumen. However, with the facilitation of a dual-lumen microcatheter, a second wire successfully passed through the stent's central lumen. Finally, the patient received a successful PCI with a stent.ConclusionA dual-lumen microcatheter–facilitated wiring technique may be useful in overcoming wiring difficulty caused by the excessive protrusion of an aorto-ostial stent into the aorta.